LITERASI PAJAK PENGHASILAN PRIBADI BAGI WNI YANG MEMILIKI NOMOR POKOK WAJIB PAJAK - Hastuti, Rini Tri; Prajogi, M Bintang; Kho, Christian (Jurnal Serina Abdimas, 2024)
The state is intensifying taxes, becoming the main source of income. All taxpayers who have a NPWP are expected to be able to calculate and report their tax bills. Tax collection system: self-assessment system requires taxpayers to report and remit their own taxes. Information regarding tax return article 21 is very useful if given early, starting from the family environment, school environment, to the general public. The Directorate General of Taxes has developed many programs that are used to provide basic information about taxes to the public from elementary schools to universities. At the basic level, namely schools, students can be given information about the important role of taxes in servicing the need for educational facilities such as: school buildings, learning facilities, operational funds for school activities, salaries for teachers and employees, and others, all of these needs will be met by state tax revenue. It is hoped that we will understand the importance of becoming a tax-compliant citizen in the future. The main PKM material that we will prepare to implement is training on the importance of understanding reporting and how to calculate Tax SPT article 21 for Indonesian citizens who have a NPWP for HARJA SMA students. Based on the above, we will provide problem solving by conducting training on how to calculate Article 21 tax returns for individual taxpayers. The implementation methods that will be used in this training include: First, conducting observations and interviews as well as observations regarding the extent to which students gain knowledge about Tax SPT article 21. Second, material regarding Tax SPT article 21 is prepared accompanied by examples of tax case questions. Third, we will explain the Module in a tutorial in two training sessions. Fourth, in the third or final training, we will give a quiz to find out how far the children understand the explanation we have given. In addition, we will also ask students to fill out a questionnaire to assess their satisfaction with the training provided. The outputs of this PKM activity are: Publications at SERINA and Posters at Research Week held by Tarumanagara University as well as HKI as additional outputs.